PhD in Public Administration and Management (By Coursework and Research) (PHDPAM-CW&R) - Kabale University (Kabale University, 2022)
is designed for those seeking academic research and teaching careers as faculty or professors in the study of governance, public administration, management and administrative sectors within Universities but also as professional career managers and administrators for a wide range of organizational contexts.